Impact of collective forestland tenure reform on household forestry production efficiency: micro-level evidence from China - Wei, Jian; Wang, Fangzheng; Xie, Tianwei; Luo, Hanxiang (Frontiers in Forests and Global Change, 2025)
Improving forestry production efficiency is crucial for advancing rural economic development and ecological modernization in China. Using panel data from 13,536 rural households in 18 counties across nine provinces during 2003 and 2007–2019, this study investigates the impact of collective forestland tenure reform on household-level forestry production efficiency. A translog stochastic frontier production function model is applied to estimate efficiency, while Tobit and mediation effect models are used to explore the underlying mechanisms. The results show that tenure reform significantly enhances forestry production efficiency, primarily by increasing production inputs, expanding forestland management scale, and improving access to credit. Further heterogeneity analysis indicates that the positive effects are more pronounced among households with pure farming livelihoods, bamboo or economic forest cultivation, and in less-developed or forest-rich regions. These findings highlight the importance of tenure security in stimulating investment incentives, promoting efficient resource reallocation, and facilitating financial inclusion in rural forestry. Policy implications include strengthening forestland tenure security, developing transparent forestland transfer markets, and innovating credit systems, with particular emphasis on supporting the sustainable management of long-cycle timber forests to balance economic benefits with ecological goals.